Peningkatan Literasi Desain Grafis Melalui Pelatihan Canva Bertema "Makariki Digital" pada Siswa SMK Negeri 4 Maluku Tengah - Jusuf Leiwakabessy; L. Nanlohy; K. Suitela; T. Luturkey; B. Lerebulan (Jurnal Informasi Pengabdian Masyarakat, 2026)
Graphic design skills are an essential competency for vocational high school (SMK) students in today’s digital age. However, initial observations at SMK N 4 Maluku Tengah indicate that the majority of students have not yet mastered the use of affordable and user-friendly design platforms such as Canva. Therefore, this community service activity aims to improve the graphic design literacy and skills of 10th-grade students through interactive training. This activity is themed “Makariki Digital,” an innovative approach that combines mastery of digital technology with the preservation of Maluku’s unique local cultural values. The activity was conducted using a participatory training method involving 30 students, and its success was measured using pre-test and post-test questionnaires. The initial evaluation (pretest) results showed that only 23.3% (7 students) had a basic understanding of Canva. After the presentation of materials and hands-on practice, the final evaluation (posttest) results surged significantly to 93.3% (28 students) who understood the material, while 6.7% (2 students) still required additional guidance. There was a 70-percentage-point increase in understanding. In conclusion, design training using the Canva platform integrated with a local context proved highly effective in boosting students’ digital design literacy.